Enhancement of thermal stability and phase relaxation behavior of chitosan dissolved in aqueous l-lactic acid: using `silver nanoparticles' as nano filler - Rana, V. K.; Pandey, Asutosh K.; Singh, Raj Pal; Kumar, B.; Mishra, Satyendra; Ha, Chang-Sik (Macromolecular Research, 2010)
Chitosan films with various compositions of silver nanoparticles were prepared by solution casting with an aqueous solution of chitosan and l-lactic acid. The chitosan/Ag nanocomposites were characterized by wide angle Xray diffraction (WAXD) and UV-vis spectroscopy. An analysis of the surface topography and size of the Ag nanoparticles (<= 100 nm) were characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM), respectively. Thermogravimetric analysis (TGA/DTA) confirmed the increase in thermal stability with increasing Ag nanoparticle content in the nanocomposites. Dynamic thermal analysis (DMA) was used to examine the phase relaxation behavior of chitosan and its nanocomposites. The conductivity of chitosan/Ag nanocomposites was considered with respect to the frequency. Contact angle measurements were used to characterize the surface twistability, surface cleanliness, and hydrophilic/hydrophobic nature of the surface.
Keywords: Chitosan; conductivity; contact angle; relaxation; silver nanoparticles

Synthesis and drug-delivery behavior of chitosan-functionalized graphene oxide hybrid nanosheets - Rana, Vijay Kumar; Choi, Myeon-Cheon; Kong, Jin-Yeon; Kim, Gwang Yeon; Kim, Mi Ju; Kim, Sun-Hee; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Macromolecular Materials and Engineering, 2011)
Chitosan-functionalized graphene oxides (FGOCs) were successfully synthesized. FGOCs were found to significantly improve the solubility of the GO in aqueous acidic media. The presence of organic groups was confirmed by means of XPS and TGA. Restoration of the sp(2) carbon network and exfoliation of graphene sheets were confirmed by Raman spectroscopy, UV-visible spectroscopy and WAXD. The SEM and AFM investigations of the resultant FGOCs showed that most of the graphene sheets were individual and few were layered. Controlled release behavior of Ibuprofen and 5-fluorouracil was then investigated. We found that FGOCs are a promising new material for biological and medical applications.
Keywords: Biocompatibility; Chitosan; drug delivery systems; functionalization of polymers; solution properties

Chitosan and chitosan-co-poly(epsilon-caprolactone) grafted multiwalled carbon nanotube transducers for vapor sensing - Rana, Vijay Kumar; Akhtar, Shamim; Chatterjee, Sudipta; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Journal of Nanoscience and Nanotechnology, 2014)
Vapor sensitive transducer films consisting of chitosan grafted (CNT-CS) and chitosan-co-polycaprolactone grafted (CNT-CS-PCL) multiwalled carbon nanotubes were prepared using a spray layer-by-layer technique. The synthesized materials (CNT-CS and CNT-CS-PCL) were characterized by Fourier transform infrared spectroscopy, C-13 CP/MAS solid state nuclear magnetic resonance spectroscopy and thermogravimetric analysis. Both CNT-CS and CNT-CS-PCL transducers were analyzed for the response of volatile organic compounds and toluene vapors. The ranking of the relative resistance (A(r)) for both chitosan based transducers were as follows: toluene < chloroform < ethanol < methanol. The CNT transducer (CNT-CS) was correlated selectively with an exponential law to the inverse of Flory-Huggins interaction parameters, chi(12). Dosing the films on the interdigitated electrodes with methanol, ethanol, chloroform and toluene vapors increased the film resistance of CNT-CS but decreased the resistance of CNT-CS-PCL compared to that of the reported transducers.
Keywords: Biocompatibility; Chitosan; MWCNTs; Poly(epsilon-caprolactone); Vapour Sensing